The effect of Metabolic Syndrome on Exercise Performance in American Football Players From a Mexican University - Morales Elizondo, Dulce Edith; Morales Corral, Pedro Gualberto; Sepúlveda Sepúlveda, Rosalinda; Sámano Pérez, Elfega; Barrera Flores, Francisco Jesús; Rizo Belloso, Emmanuel (2019)
PURPOSE: To demonstrate the effect of the metabolic syndrome (MetSyn) upon the physical performance of American Football Players in a Mexican college team. METHODS: Seventy six players were included in the study, thirteen had MetSyn (21.7±1.5 yrs) and sixty three did not (21.8±1.5 yrs). Comparisons between the physical performance and the presence / absence of MetSyn; The players were grouped by body mass and type of execution on the field, in Group 1: Offensive and Defensive Linemen (OL and DL) and Tight ends (TE); Group 2: Running Backs (RB), Linebackers (LB) and Quarter Backs (QB); Group 3: Wide Receivers (WR), Kickers (K), Strong Safeties (SS) and Corner Backs (CB). The physical performance tests measured were: Maximum strength, explosive strength, Isometric hand strength, muscular resistance, power of upper and lower body, lumbar flexibility, agility, speed and cardiovascular resistance RESULTS: The results of group 2 in the bench press test, revealed a better performance in the players with MetSyn, suggesting a possible favorable association with this syndrome an the maximal chest strength. Group 2 showed as well a lower athletic performance of the speed, agility, flexibility and muscular resistance tests in the MetSyn players which can associate this syndrome negatively to these motor skills.